(untitled) (Research, Society and Development, 2023)
This search aims to evaluate the corrosivity of AISI 1020 steel in clayey soil through microbiological analyzes and the mass loss technique. Through the results obtained, according to the identification methodology of the Bergey manual, the presence of two microorganisms was verified, Acidithiobacillus thiooxidans and ferrooxidans , responsible for the biocorrosion process , in addition to filamentous fungi. The presence of these bacteria does not generate a classification for the soil, however, it is known that they can accelerate the corrosion process when in contact with a metallic structure. Regarding the mass loss rate, a criterion used to simulate the assessment of corrosivity in pipes, NACE Standard RP-07-75 was adopted, which defined the intensity of the corrosive process, obtaining as a result for the sterilized sample a value considered low, since it was free of microbial activities and any other contaminating factor, but for the sample without sterilization, the soil was classified as having severe potential. Therefore, this research sought to correlate the characteristics of the soil representative of the Amazon with a process of corrosion of buried pipes due to the presence of microorganisms, which would correspond to a microbiological corrosion. Although, in many cases, there is suspicion of the accuracy of corrosion monitoring techniques, mass loss and microbiological identification techniques were used, which had a positive result in relation to the microbiological one.